Formation of some elements of the right to defence in misdemeanour proceedings - Sowiński, Piotr Krzysztof (Ius Novum, 2024)
The text analyses normative solutions concerning the right to defence in Polish proceedings in cases of offences. It discusses the formation of selected elements of the right to defence, from the pre-war solutions to modern times. The author highlights the autonomy of the solutions in force in the 2001 Code of Proceedings in Misdemeanour Cases, and their similarities to the right to defence in criminal cases, constituting the most comprehensive model of this right.